Dr. Victor Sterki as a Malacologist - Ralph W. Dexter (Hello World!, 1967)
Dr. Victor Sterki (1846-1933) was a well-known physician, conchologist, and naturalistin the eastern Ohio- western Pennsylvania region. He was born in 1846 at Solothurn, Switzerland, where he attended the local gymnasium and lyceum during his youth. He pursued medical studies 1868-73 at the University of Bern where he eventually received the M.D. degree in 1878. While a medical student he collected plants and shells as a hobby and took formal courses in botany and zoology as well as in medicine. After passing the government examination for the practice of medicine, he servedin the eye hospital at the University of Bern until 1874 when he entered private practice. Following a period of illness he studied protozoology at Munich, Germany, and wrote his doctoral dissertation on a study of ciliated protozoans.